All-electronic frequency stabilization of a DFB laser diode - Asmari, A.; Hodgkinson, Jane; Chehura, Edmon; Staines, Stephen E.; Tatam, Ralph P. (Optical Society of America, 2017)
A laser diode’s junction voltage is a sensitive measure of its temperature and can be used in a thermal control feedback loop. To compensate for the temperature dependence of the laser’s internal resistance, we have measured the dynamic resistance, ∂V/∂I, by modulating the injection current and measuring the demodulated voltage. The junction voltage was thus controlled while operating at fixed DC injection current. Over an external temperature range of 15°C to 35°C, this stabilised the centre frequency (wavelength) of a 1651 nm DFB laser diode with a residual mean frequency shift of 60 MHz (0.5pm), less than the uncertainty on the centre frequency of 80 MHz (0.7 pm). Under the same conditions, conventional thermistor control gave a systematic wavelength shift of −8.4 GHz (−76 pm), and control of the uncompensated forward voltage gave a shift of 9.9 GHz (90 pm).
Keywords: Diode lasers; Laser stabilization; Thermal effects; Spectroscopy, diode lasers